Evaluasi Millennium Development Goals (MDGs) dalam Menanggulangi Kemiskinan dan Kelaparan Menuju Sustainable Development Goals (SDGs) di Kota Medan - Clara Adeline Marpaung; Muhammad Daffa Raihan Firdaus; Indah Prabawati; Firre An Suprapto (Pustaka Digital Indonesia, 2026)
This study discusses efforts to reduce poverty and hunger in Medan City through the achievement of the Millennium Development Goals (MDGs) targets as the first step towards the Sustainable Development Goals (SDGs). The research method used is in the form of a quantitative descriptive approach by utilizing secondary data from various regional development indicators. Analysis was carried out on poverty conditions, employment opportunities, labor productivity, and community nutritional status to see the development of population welfare. The findings of the study show that the poverty rate in Medan City has a tendency to decline in recent years even though the achievement has not been fully in accordance with the set target. On the other hand, indicators of the depth and severity of poverty show an improvement in the economic conditions of the poor. Labor productivity has also increased in line with regional economic growth, although the provision of jobs still needs to be expanded. In addition, the nutritional condition of toddlers shows quite good results with low rates of malnutrition and malnutrition. In general, the implementation of MDGs-based development programs in Medan City has had a positive impact and can be a foothold in supporting the implementation of the SDGs in the future